Model Tata Kelola Berbasis Green Production untuk Mendorong Keberlanjutan Organisasi dan Kepatuhan - Melani Melani (Asian Journal of Multidisciplinary Research, 2025)
This study addresses a persistent gap between organizations’ green production intentions and the consistent realization of organizational sustainability and environmental compliance. The purpose of this research is to develop a conceptual model of green production governance that can drive sustainability and compliance through structured governance mechanisms. Using a qualitative library-based research design, the study synthesizes relevant literature as primary and secondary data, focusing on three key constructs: Green Production Governance, Organizational Sustainability, and Environmental Compliance. Data were collected through systematic reading of books, journal articles, and prior research, and were analyzed using content analysis to identify recurring patterns and conceptual relationships across sources. The study concludes that effective green production governance—reflected in clearly assigned responsibilities, operational procedures, monitoring, auditing, corrective actions, and organizational learning—enables more stable sustainability outcomes and strengthens compliance over time. The findings provide an initial governance-oriented framework for future empirical testing and practical organizational improvement.